Syllidae (Annelida: Phyllodocida) from Lizard Island, Great Barrier Reef, Australia - Aguado, M. Teresa; Murray, Anna; Hutchings, Pat (Zootaxa, 2015)
Thirty species of the family Syllidae (Annelida, Phyllodocida) from Lizard Island have been identified. Three subfamilies (Eusyllinae, Exogoninae and Syllinae) are represented, as well as the currently unassigned genera Amblyosyllis and Westheidesyllis. The genus Trypanobia (Imajima & Hartman 1964), formerly considered a subgenus of Trypanosyllis, is elevated to genus rank. Seventeen species are new reports for Queensland and two are new species. Odontosyllis robustus n. sp. is characterized by a robust body and distinct colour pattern in live specimens consisting of lateral reddish-brown pigmentation on several segments, and bidentate, short and distally broad falcigers. Trypanobia cryptica n. sp. is found in association with sponges and characterized by a distinctive bright red colouration in live specimens, and one kind of simple chaeta with a short basal spur.